Corrosion monitoring of friction welded joints results between low carbon steel-SS 202 - Ahmad Kafrawi Nasution; M Arif Fadillah; Legisnal Hakim (Universitas Muhammadiyah Yogyakarta, 2021)
Pada penelitian ini, pemantauan korosi dilakukan pada sambungan las gesekan baja karbon rendah dan baja tahan karat austenitik (SS 202) yang disimulasikan dalam larutan biologis. Penelitian ini bertujuan menghitung laju korosi sambungan las gesek baja karbon rendah dan SS 202 serta mengevaluasi kekasaran permukaan yang terjadi pada zona pengelasan. Dari hasil sambungan las, dibuat sampel uji korosi dengan mewakili zona pengelasan. Sebelum perendaman, permukaan sampel dibersihkan dan dipoles sebelum perendaman menggunakan larutan elektrolit NaCl 0,9wt.%. Percobaan dijalankan pada 2, 4, 6, dan 8 minggu masing-masing sampel. Hasil penelitian menunjukkan bahwa laju korosi sambungan las gesek baja karbon rendah dan SS 202 tertinggi sebesar 0,0167 mm/tahun, dan terendah 0,0127 mm/tahun. Pada saat yang sama, area sambungan las yang memiliki kekasaran permukaan tertinggi terjadi pada zona plastis. Disimpulkan bahwa seluruh zona pengelasan menunjukkan potensi korosi yang seragam kecuali zona plastis yang menunjukkan perilaku korosi galvanik. ABSTRACT In this study, corrosion monitoring was carried out in the friction welded joint of low carbon steel and austenitic stainless steel (SS 202) simulated in a biological solution. This study aims to calculate the corrosion rate of friction welding joints of low carbon steel and SS 202 and evaluate the surface roughness that occurs in the welding zone. From the results of welded joints, corrosion test samples were made by representing the welding zone. Prior to immersion, the surface of the sample was cleaned and polished before immersion using a 0.9wt.% NaCl electrolyte solution. Experiments were run at 2, 4, 6, and 8 weeks of each sample. The results showed that the corrosion rate of friction welding joints for low carbon steel and SS 202, the highest was 0.0167 mm/year, and the lowest was 0.0127 mm/year. At the same time, the welded joint area that has the highest surface roughness occurs in the plasticized zone. It was concluded that the entire welding zone showed uniform corrosion potential except for the plasticized zone, which showed galvanic corrosion behavior.